Off the wall : political posters of the Lebanese Civil War. - Maasri, Zeina (I.B. Tauris ;, 2009)
n this lavishly illustrated work, Zeina Maasri tells the tumultuous story of the struggle for Lebanon through the poster wars which raged on its streets. From 1975 to 1990, different factions in Lebanon's civil conflict flooded the streets with posters to mobilize their constituencies, undermine their enemies, and create public sympathy for their cause. Showcased here for the first time, the posters display a dramatic clash of cultures, ideologies and meanings. Maasri shows how the iconography of the posters changed throughout the war, and links this to changing political identities and imagined communities. She explores the factions' different aesthetic influences; from modern Arab visual culture to Latin America and revolutionary Iran. Combining in-depth knowledge of the local context with fascinating insights into the semiotics of visual media, "Off the Wall" is a highly original contribution to our understanding of visual culture, civil conflict, and the politics of the Middle East -- Présentation de l'éditeur.